The PESCP-BIOCON in Northwest Panay strategies in biodiversity conservation - Dacoroon, Minihaha Cadungog
This is a study on the biodiversity conservation strategies implemented by the PESCP-BIOCON in five selected barangays in Northwest Panay Peninsula. Specifically, the study aims to (a)describe the biodiversity conservation strategies implemented by the PESCP-BIOCON; (b)determine local people's knowledge of the biodiversity conservation strategies; (c)identify the problems encountered by the PESCP-BIOCON Staff in the implementation of the biodiversity conservation strategies; (d)identify the approaches used by the PESCP-BIOCON Staff to counter the problems in the implementation of the project. Data needed for this study was gathered primarily through interviews using two sets of interview instruments. Library research was also done for supplementary information. The data was analyzed using descriptive statistics. Results of the study show that majority of the respondents are aware of the existence of the PESCP-BIOCON. However, their awareness varies on these three aspects: PESCP, BIOCON, and community organizers. Majority of those who are aware of the existence of the PESCP-BIOCON are aware of its presence in their respective barangays. The majority of those who are aware of its presence participate in the activities of PESCP-BIOCON and also anticipate participating in future activities. Respondents perceive that biodeiversity conservation is important not only for the present generation but for the future as well. They further believe that PESCP-BIOCON contributed a lot in their knowledge of the importance of biodiversity conservation. On the other hand, local people's limited understanding of the importance of biodiversity conservation is a major problem encountered by the PESCP-BIOCON staff. Thus, community education plays a vital role in the implementation of biodiversity conservation project in Northwest Panay.